Competing mortality risks among women aged 50–79 years when diagnosed with invasive breast cancer, Queensland, 1997–2012. (October 2018) - Dasgupta, Paramita; Aitken, Joanne F.; Pyke, Christopher; Baade, Peter D.
Abstract: Background: Understanding the burden of competing (non-breast cancer) mortality is important for the growing number of breast cancer survivors. We quantity these patterns, and the impact of two leading non-cancer causes of death, within ten years of breast cancer diagnosis. Methods: Population based cancer registry study of 23, 809 women aged 50–79 diagnosed with first primary breast cancer in Queensland, Australia, 1997 to 2012 with additional data linkage to identify individual non-cancer mortality causes. Flexible parametric competing-risks models were used to estimate the crude and adjusted probabilities of death. Results: While overall mortality increased with age at diagnosis, this effect was strongest for non-cancer (such as cardiovascular and cerebrovascular disease) mortality. Women diagnosed with advanced breast cancer had a higher crude probability of breast cancer death (23.1% versus 4.5% for localised) but similar probability of competing mortality (11.6% versus 11.3%). Within each category of spread of disease, the probability of breast-cancer deaths remained relatively constant with age, while the probability of competing deaths increased. The 10-year probability of dying from breast cancer was 3.7%, 4.2% and 5.6% among women with localised disease aged 50 to 59, 60–69 and 70–79 respectively, but 3.1%, 7.8% and 22.9% for competing mortality. Increasing age, advanced disease and being unpartnered were independently associated with increased risk of breast cancer and competing deaths. Conclusions: Promotion of improved health behaviors after a cancer diagnosis and development of individualized strategies for clinical management should be prioritized as part of optimal care for breast cancer survivors. Highlights: Population-based study of 23, 809 women with invasive breast cancer. Risk of non-cancer mortality was lower than for the general female population. Increasing mortality effect by age was strongest for non-cancer mortality. Spread of disease had no association with risk of non-breast cancer mortality. Risk of non-cancer mortality increased with survival time.